2018
DOI: 10.1016/j.pharep.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 and serum amyloid P inversely regulate fibrocyte differentiation by targeting store-operated Ca 2+ channels

Abstract: IL-4 and SAP reversely regulates cultured fibrocytes differentiation in vitro by respectively promoting or inhibiting the expression and activity of SOC channels in fibrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…27 Fibrocytes also express the chemokine receptors CCR2, CCR3, CCR5, CCR7, CXCR4, CXCR6, and CX3CR1, host defense Fc receptors for immunoglobulin G (CD32 and CD64), antigen presentation and costimulatory molecules of lymphocyte activation (major histocompatibility complex [MHC] class I and II/CD80 and CD86), and cell surface enzymes (CD10 and CD13). 24,25,27,[36][37][38] The complete list of fibrocytes markers is presented in Table 1. 8,24,25,39 In the majority of studies reported, fibrocytes were identified by a combination of expressed markers, for example, the simultaneous expression of CD34 or CD45 or CD11b and collagen type I or collagen type III.…”
Section: Fibrocytes Markersmentioning
confidence: 99%
See 3 more Smart Citations
“…27 Fibrocytes also express the chemokine receptors CCR2, CCR3, CCR5, CCR7, CXCR4, CXCR6, and CX3CR1, host defense Fc receptors for immunoglobulin G (CD32 and CD64), antigen presentation and costimulatory molecules of lymphocyte activation (major histocompatibility complex [MHC] class I and II/CD80 and CD86), and cell surface enzymes (CD10 and CD13). 24,25,27,[36][37][38] The complete list of fibrocytes markers is presented in Table 1. 8,24,25,39 In the majority of studies reported, fibrocytes were identified by a combination of expressed markers, for example, the simultaneous expression of CD34 or CD45 or CD11b and collagen type I or collagen type III.…”
Section: Fibrocytes Markersmentioning
confidence: 99%
“…13,45,46 Niedermeier et al 26 suggest that the interaction between Th2 cytokines and fibrocytes precursor cells occurs via a mTOR-PI3 kinase dependent pathway. Zhong et al 36 demonstrate that IL-4 facilitates the in vitro differentiation of fibrocytes by increasing the activity and expression of store-operated Ca 2+ entry (SOCE) channels. In their studies, blockage of SOCE channels with SKF-96365 significantly inhibits IL-4induced differentiation of fibrocytes.…”
Section: Factors That Promote and Inhibit Fibrocyte Differentiationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, knock‐down of Orai1 channels inhibited TGF‐β1‐induced epithelial–mesenchymal transition, [Ca 2+ ] i influx and phosphorylation of SMAD2/3 (Mai et al, ). Peripheral blood monocyte‐derived IL‐4‐dependent fibrocyte differentiation was dependent on store‐operated Ca 2+ channels and increased the expression of both STIM1 and Orai1 (Zhong et al, ). Therefore, targeting these channels in fibrosis might reduce trafficking of circulating fibrocytes into fibrosing organs such as the lung in IPF, where increased circulating fibrocytes are an indicator of disease activity and a predictor of early mortality (Moeller et al, ; Wright et al, ).…”
Section: Introductionmentioning
confidence: 99%